MAIN INDICATORS OF THE OXIDANT-ANTIOXIDANT SYSTEM AND THEIR RELATIONSHIP WITH THE FORCE OF THE RESPIRATORY MUSCLES IN ADULT PATIENTS WITH COMMUNITY-ACQUIRED PNEUMONIA - Bereznyakov, V. I. (International Journal of Medicine and Medical Research, 2021)
Background. Currently, pneumonia ranks 4-5 rate in the world in the structure of death causes after cardiovascular and cancer diseases, cerebrovascular pathology, injuries and poisonings. Objective. The aim of the study was to evaluate the indicators of the oxidative-antioxidant system and their relationship with the strength of the respiratory muscles in adult patients with community-acquired pneumonia. Methods. The study was carried out in the period 2017-2020 on the basis of the therapeutic department of the Municipal non-profit enterprise "City Clinical Multidisciplinary Hospital № 25" of Kharkiv City Council. The study involved 52 adult patients with CAP aged 18 to 80 years. The control group consisted of 20 apparently healthy humans. It was determinated the activity of malondialdehyde, catalase and superoxide dismutase, level of reduced glutathione, glutathione reductase and glutathione peroxidase. The assessment of the RM strength was investigated by recording the maximum static pressures at the level of the mouth and nose with “closed” airways using a MicroRPM apparatus on the 1st and 10th days of illness. Results. Dysfunction of expiratory respiratory muscles prevailed in patients with non-severe CAP, and inspiratory respiratory muscles in patients with severe CAP. Were established significant negative correlations of malondialdehyde with indicators of respiratory muscles strength and positive correlations with glutathione reductase, glutathione peroxidase, catalase, and superoxide dismutase. Conclusions. The presence of relationships between pro- and antioxidant indicators and respiratory muscles strength complements the concept of the body's systemic response on pulmonary inflammation – one of the markers of respiratory muscles dysfunction. KEYWORDS: community-acquired pneumonia, respiratory muscles, oxidative-antioxidant system.